Analysis of Strengthening MSMes in the Digitalization Era to Encourage an Even and Sustainable Economy in Rural (Non-Urban) Areas - Dina Nadiyah Faiqoh; Agus Kusnawan; Ravindra Safitra Hidayat; Slamet Mudjijah (Asian Journal of Management Analytics, 2026)
The purpose of this study is to assess the readiness of MSMEs in rural areas to face digitalization. Research methods include observation and interviews with MSME owners in East Lampung to understand the challenges of digitalization, collect profile data, and utilize fintech to support a sustainable economy. Research in East Lampung shows that many MSMEs have adopted the QRIS payment system and social media, but are still limited in online delivery. Digital awareness and transaction costs are also obstacles to expansion. Encouraging digitalization can generate more inclusive and sustainable local economic growth. Recommendations for this study: The government, educational institutions, and banks need to implement digital literacy training for MSMEs, establish digital communities, and conduct research to assess the effectiveness of programs and their impact on economic growth and financial inclusion in East Lampung.